117k views
1 vote
Simplify the following expression:
4n - m + 3p + 2m - n - p

Simplify the following expression: 4n - m + 3p + 2m - n - p-example-1

2 Answers

5 votes

Answer:


= 3n + m + 2p (first option)

Explanation:


4n - m + 3p + 2m - n - p


4n - n = 4n - 1n = (4 - 1)n = 3n


3n - m + 3p + 2m - p


- m + 2 = - 1m + 2m = ( - 1 + 2)m = 1m = m


3n + m + 3p - p


3p - p = 3p - 1p = (3 - 1)p = 2p


= 3n + m + 2p

User Chris Pietschmann
by
5.4k points
2 votes

Answer:

The choose One

3n+m+2p

I hope I helped you^_^

User Zlata
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.